1997
DOI: 10.1242/dev.124.7.1281
|View full text |Cite
|
Sign up to set email alerts
|

Heart and neural tube defects in transgenic mice overexpressing the Cx43 gap junction gene

Abstract: Transgenic mice were generated containing a cytomegaloviral promoter driven construct (CMV43) expressing the gap junction polylpeptide connexin 43. RNA and protein analysis confirmed that the transgene was being expressed. In situ hybridization analysis of embryo sections revealed that transgene expression was targeted to the dorsal neural tube and in subpopulations of neural crest cells. This expression pattern was identical to that seen in transgenic mice harboring other constructs driven by the cytomegalovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…We have opted for an inducible genetic system because CMV-driven ubiquitous Cx43 overexpression in mice was reported to cause morbidity and postnatal mortality due to neural tube and conotruncal heart defects [ 29 ], a phenotype which was reminiscent of Cx43 KO models [ 21 , 47 ]. We tested our genetic construct in ES cells, as well as HeLa cells and 3T3-fibroblasts, and observed no leakiness in the absence of Cre, whereas AAV-Cre-mediated excision of the floxed stop cassettes resulted in Cx43 overexpression in cells with and without endogenous Cx43 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have opted for an inducible genetic system because CMV-driven ubiquitous Cx43 overexpression in mice was reported to cause morbidity and postnatal mortality due to neural tube and conotruncal heart defects [ 29 ], a phenotype which was reminiscent of Cx43 KO models [ 21 , 47 ]. We tested our genetic construct in ES cells, as well as HeLa cells and 3T3-fibroblasts, and observed no leakiness in the absence of Cre, whereas AAV-Cre-mediated excision of the floxed stop cassettes resulted in Cx43 overexpression in cells with and without endogenous Cx43 expression.…”
Section: Discussionmentioning
confidence: 99%
“…To address these aspects, we have taken a different approach from KOs by generating an inducible Cx43 overexpression model in pluripotent mouse embryonic stem (ES) cells. This strategy was chosen, since earlier experiments in mice illustrated that ubiquitous overexpression of Cx43 resulted in embryonic and postnatal morbidity and reduced postnatal viability [ 29 ]. We reasoned that Cx43 overexpression could also have (adverse) effects on the propagation, development, and differentiation of native cells and/or ES cell-derived cell populations in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the GJA5 was downregulated in CM-A in CAD HF, and Vozzi et al ( 57 ) found that the connexin40 was expressed higher in atrium than that in ventricle in human heart. However, the expression level of GJA1 was enhanced in DCM HF, and some studies had reported that both decrease and increase of GJA1 could cause abnormal heart function ( 58 , 59 ). Previous study also showed that the downregulation expressions of connexin40 and connexin43, which disturbed the Wnt signaling and caused the calcium signal dysregulation ( 36 , 37 , 60 ).…”
Section: Discussionmentioning
confidence: 99%
“…Нокаут гиалуронансинтазы-2 (Has2), одного из членов семейства трех генов, участвующих в синтезе гиалуронана у млекопитающих, нарушает развитие эндокардиальной подушки сердца (производное клеток нервного гребня) (tuber endocardiale atrioventriculare, LNE), сформированный дефект связан с ингибированием миграции клеток сердечного нервного гребня (CarNCCs) [128][129][130][131][132].…”
Section: -1879 ггunclassified